Flying saucers: an introduction - Jenkins, Timothy (Images of elsewhere, 2025)
"'Jenkins' meticulously researched essay will change how you think about UFOs. The interesting question is not whether flying saucers are real or fake, but rather, in what sociotechnical world were such sightings plausible? A fascinating exploration of military vigilance, technological innovation and changing standards of evidence in the mid-twentieth century.' - Matei Candea, Professor of Social Anthropology, University of Cambridge. Flying saucers emerged as objects of concern to an intelligence unit operating within the US Air Force in the early Cold War. This book tracks the progressive identification and conceptualization of the UFO (Unidentified Flying Object) through contemporary documents and traces the fate of the 'interplanetary hypothesis'. This small-scale history relates to extraordinary developments in the period in both weapons and communications technologies, as powered rocket flight beyond the atmosphere became a possibility and home radar had to be expanded to detect and meet the threat of enemy missiles. In this context, sightings provoked increasing division among investigators as well as growing public interest in flying saucers, and official policy shifted focus from research to management of reactions to these objects. All the features of early UFO sightings have continued into the present with controversies over UAPs (Unidentified Aerial Phenomena)"-- Provided by publisher